Strategi Pemasaran Digital dalam Meningkatkan Ekuitas Merek pada UMKM Sandangs - Pangestu, Ilham Asta; Nugroho, Rusdi Hidayat (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This journal discusses digital marketing strategies used to enhance the brand equity of MSMEs (Micro, Small, and Medium Enterprises) on the Sandangs platform (PT Tirta Cipta Teknokreatif) in Surabaya City. In the constantly evolving digital era, MSMEs need to adopt effective marketing strategies to expand their market reach and build customer trust in their brand. Digital marketing includes various elements such as social media, websites, search engines, and online advertising campaigns. This journal presents various digital marketing strategies that are crucial for MSMEs and can be implemented to increase brand awareness. The aim of this journal is to deeply understand the role of digital marketing strategies in enhancing brand equity for MSMEs. It is hoped that by adopting relevant and effective strategies, MSMEs can harness the potential of the digital market to achieve greater success. This journal uses a literature study research method through a qualitative descriptive approach, where data is obtained from secondary sources based on previous research. Based on the results of this literature study, it is found that effective and relevant digital marketing strategies influence brand equity for a specific product, especially for MSMEs.